Analysis on ergonomic factors and workload of female civil government employees in the local government offices of Sorong - Talakua, Febry; Etnis, Baktianita Ratna; Nasedum, Ivana Ribka; Bambungan, Yulinda Margaret; Lerebulan, Exaudian F. (International journal of health sciences, 2022)
Background: Based on the initial survey conducted by researchers, ergonomic problems were found in the female Civil Government Employees (Pegawai Negeri Sipil, PNS), including the fact that most female Civil Government Employees are old. Most female Civil Government Employees went to the office without having breakfast. The desks and chairs at work were not designed ergonomically. The work station was located in the fourth floor without an escalator, causing fatigue. The room temperature and lighting are unfitting. These problems are disadvantageous for their workloads. Objectives: The objective of this research is to find out the influence of ergonomic factors on female Civil Employees’ workloads in the Local Government Offices of Sorong City. Methods: The method applied in this research is the analytical survey with a cross-sectional design. The applied sampling method was random sampling stratification, with 104 samples. The data is collected using questionnaires. The data analysis includes univariate, bivariate, and multivariate, applying the Chi Square (X2) test and multivariate analysis with logistic regression. Research Results: The bivariate test result shows that workloads are influenced by the following factors: age (p=0.002), nutritional status (p=0.002), working behavior (p=0.003), tools layout (p=0.001), working environment (p=0.001).